2020
DOI: 10.31234/osf.io/j6y5d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Children’s Discrete Proportional Reasoning Is Related to Inhibitory Control and Enhanced by Priming Continuous Representations

Abstract: Children can successfully compare continuous proportions as early as age 4, yet struggle to compare discrete proportions least to age 10, especially when the discrete information is misleading. This study examined whether inhibitory control contributes to individual differences in discrete proportional reasoning and whether reasoning could be enhanced by priming continuous information. Forty-nine second-graders completed two tasks. In the Hearts and Flowers (H&F) task, a measure of inhibition, children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…While these results pointed towards the importance of semantic inhibition for rational number understanding, two recent studies have found that the Hearts and Flowers task, a developmentally appropriate measure of response inhibition (Wright & Diamond, 2014), also relates to rational number outcomes in children. Abreu-Mendoza, Coulanges, Ali, Powell, and Rosenberg-Lee (2020) found that better inhibitory control was related to better performance on a discrete proportional reasoning task, specifically when the number of segments conflicted with the correct response. Ren and Gunderson (2021) report that children with better inhibitory control displayed less use of an incorrect whole number strategy during a decimal comparison, training task, and also at post-test.…”
Section: Types Of Inhibitory Control and Their Contributions To Rational Number Processingmentioning
confidence: 96%
“…While these results pointed towards the importance of semantic inhibition for rational number understanding, two recent studies have found that the Hearts and Flowers task, a developmentally appropriate measure of response inhibition (Wright & Diamond, 2014), also relates to rational number outcomes in children. Abreu-Mendoza, Coulanges, Ali, Powell, and Rosenberg-Lee (2020) found that better inhibitory control was related to better performance on a discrete proportional reasoning task, specifically when the number of segments conflicted with the correct response. Ren and Gunderson (2021) report that children with better inhibitory control displayed less use of an incorrect whole number strategy during a decimal comparison, training task, and also at post-test.…”
Section: Types Of Inhibitory Control and Their Contributions To Rational Number Processingmentioning
confidence: 96%
“…A final question afforded by this data set was assessing the contribution of different measures of inhibitory control. Prior work has found associations between various Stroop tasks and rational number outcomes (Avgerinou & Tolmie, 2019;Coulanges et al, 2021;Gómez et al, 2015), and also the Hearts and Flowers task (Abreu-Mendoza et al, 2020;Ren & Gunderson, 2021). In fact, the Flanker task is the only measure of inhibitory control studied so far that has not been found to be associated with rational number performance (Matthews et al, 2016;Park & Matthews, 2021).…”
Section: Inhibitory Control Supports Fraction Comparison Across Grade...mentioning
confidence: 97%
“…The majority of studies examining inhibitory control have found positive associations with rational number outcomes (Abreu-Mendoza et al, 2020;Avgerinou & Tolmie, 2019;Coulanges et al, 2021;Gómez et al, 2015;Ren & Gunderson, 2021), but not all (Matthews, Lewis, & Hubbard, 2016;Park & Matthews, 2021). Notably, Matthews et al (2016) found that inhibitory control was not related to performance on a non-symbolic fraction comparison task or to conceptual understanding of rational numbers, nor was it related to symbolic fraction comparison (Park & Matthews, 2021).…”
Section: Executive Functions and Fraction Understandingmentioning
confidence: 98%
See 2 more Smart Citations